PENGARUH KOMPETENSI PEGAWAI, KECERDASAN EMOSIONAL DAN KOMITMEN SEBAGAI KINERJA PEGAWAI PADA DINAS KEBUDAYAAN DAN PARIWISATA KOTA PAREPARE - Nurasisah, Nurasisah; Ramli, Mansyur; Alam, Roslina (Universitas Muhammadiyah Parepare, 2021)
This study aims to: (1) them the influence of competence on employee performance at the DINAS KEBUDAYAAN DAN PARIWISATA KOTA PAREPARE (2) to examine the impact of emotional intelligence on employee performance at the DINAS KEBUDAYAAN DAN PARIWISATA KOTA PAREPARE (3) to examine the effect of commitment on employee performance at the DINAS KEBUDAYAAN DAN PARIWISATA KOTA PAREPARE. This study made use of a questionnaire data collection technique with a population of 30 people, and the entire population was sampled. The sampling method uses total sampling. This research was conducted for one month, then data analysis used multiple linear regression data analysis using SPSS 21 software. The results showed that (1) staff member competency had an in part significant impact on the performance of the staff member of the DINAS KEBUDAYAAN DAN PARIWISATA KOTA PAREPARE (2) emotional intelligence does not have a partially significant effect on the performance of the staff member of the DINAS KEBUDAYAAN DAN PARIWISATA KOTA PAREPARE. (3) commitment has a partially significant effect on the performance of the employees of the DINAS KEBUDAYAAN DAN PARIWISATA KOTA PAREPARE. (4) competence, emotional intelligence, and commitment have a significant effect simultaneously on the performance of the employees of the DINAS KEBUDAYAAN DAN PARIWISATA KOTA PAREPARE.